2004
DOI: 10.1111/j.1537-2995.2004.04088.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with pertrochanteric hip fracture may benefit from preoperative intravenous iron therapy: a pilot study

Abstract: The administration of IV iron sucrose seems to reduce ABT requirements in patients with PHF and is associated to lower postoperative morbidity. The possible mechanisms involved in these effects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 32 publications
8
118
3
2
Order By: Relevance
“…iron can correct iron deficiency anaemia before elective orthopaedic surgery 67 and reduce rates of ABT, postoperative infection, and mortality in patients with hip fracture, compared with historical controls. 68 69 Another case series found that the perioperative use of i.v. iron in conjunction with ESA therapy in anaemic patients with hip fracture (Hb levels of ,13 g dl 21 ) reduced the proportion of patients requiring transfusion, the number of units transfused, and the rate of postoperative infections compared with a parallel control group.…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…iron can correct iron deficiency anaemia before elective orthopaedic surgery 67 and reduce rates of ABT, postoperative infection, and mortality in patients with hip fracture, compared with historical controls. 68 69 Another case series found that the perioperative use of i.v. iron in conjunction with ESA therapy in anaemic patients with hip fracture (Hb levels of ,13 g dl 21 ) reduced the proportion of patients requiring transfusion, the number of units transfused, and the rate of postoperative infections compared with a parallel control group.…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron. [26][27][28] Conversely, a retrospective study focusing only on postoperative IV iron administration found that its use significantly reduced the percentage of patients receiving a transfusion (11.5% vs 26.4%, P = 0.001). 29 These findings are further complicated by subanalyses of 2 of the aforementioned trials showing that patients with preoperative hemoglobin concentrations greater than 12 g/dL required fewer transfusions compared with those in control groups.…”
Section: Perioperative Settingmentioning
confidence: 99%
“…No standard dose exists in this setting; however, total doses of 200 to 600 mg of iron sucrose (100-200 mg every 48 hours for 2-3 doses beginning on the day of admission) perioperatively have been reported in studies focusing on IV iron. [26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron.…”
Section: Perioperative Settingmentioning
confidence: 99%
“…En cirugía, la experiencia se ha centrado con la corrección preoperatoria de la anemia por déficit de hierro debido a Optimización de la hemoglobina preoperatoria con hierro intravenoso 7 miomas 20 o neoplasia de colon 21 , o cirugía traumatológica y ortopédica 22,23 . En el campo de la cirugía ortopédica solo hay disponibles estudios observacionales con tamaños muestrales de 21 24 , 20 25 , y 21 26 pacientes.…”
Section: Discussionunclassified